THE EFFECTIVENESS OF GIVING IRON SUPPLEMENTS (FE) ON ANEMIA EVENTS IN PREGNANT WOMEN IN TANETE PUBLIC HEALTH CENTER - Nurul Hidayah Bohari; Sumarni; Haerani; Yuliana Yeni; Nurhalisa (Journal Of Midwifery And Nursing Studies, 2019)
Anemia is a condition in which the number and size of blood cells or hemoglobin concentration is below normal limits, consequently it can disrupt the capacity of the blood to carry oxygen around the body. To determine the effectiveness of iron supplementation in the incidence of anemia in pregnant women at the clinic at the Tanete Public Health Center. This study is a research by taking data by taking samples by determining specific characteristics according to the research criteria so that it is expected to be able to answer research problems regarding the effectiveness of iron supplementation (fe) on the incidence of anemia in pregnant women at the Tanete Public Health Center. Data in this study is obtained through note-taking techniques using a spreadsheet with a sample size of 42 respondents with the purposive sampling method. The research variable under study is a single variable. After administration of iron tablets or (Fe) 38 pregnant women (90.5%) with normal HB flasification and 3 pregnant women (7.1%) with mild HB flasification. From the results of the study, 42 samples of pregnant women who have anemia and after being given iron tablets (Fe) experience an increase in HB levels by 38 (90.5%), here it shows that iron (Fe) tablets are effective in pregnant women with anemia.